(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The use of multimedia educational resources allows students to acquire modern knowledge, effectively organize the educational process and ensure a change in the quality of education. This article discusses the creation and use of multimedia educational resources in teaching computer science and information technology.